(untitled) (Web of Teachers: Inderscience Research, 2025)
The problem of modern education – formation of professional and creative abilities of future teachers – is investigated. The relevance of the acmeological approach implementation is presented in order to provide pedagogical conditions for effective formation of professional and creative abilities in the educational process at the university. The stages of the process of development of formation of professional and creative abilities of teachers are developed taking into account the acmeological theory of maturity. The author comes to the conclusion that the application of the acmeological approach acts as a means and condition for the formation of the personality of a competent teacher, a professional.